Anti-biofilm activity of marine algae-derived bioactive compounds - Behzadnia, Asma; Moosavi-Nasab, Marzieh; Oliyaei, Najmeh (Frontiers in Microbiology, 2024)
A large number of microbial species tend to communicate and produce biofilm which causes numerous microbial infections, antibiotic resistance and economic problems for different industries. Therefore, advanced anti-biofilms are required with novel attributes and targets such as quorum sensing communication system. Meanwhile, quorum sensing inhibitors as promising anti-biofilm molecules result in the inhibition of particular phenotypes expression blocking cell-to-cell communication, which would be more acceptable than conventional strategies. Many natural products are identified as antibiofilm agents from different plants, microorganisms, and marine. Marine algae are promising sources of broadly novel compounds with anti-biofilm activity. Algae extracts and their metabolites such as sulfated polysaccharides (fucoidan), carotenoids (zeaxanthin, and lutein), lipid and fatty acids (γlinolenic acid and linoleic acid) and phlorotannins can inhibit the cell attachment, reduce the cell growth, interfering in quorum sensing pathway by blocking related enzymes, disruption of extracellular polymeric substances. In this review, the mechanisms of biofilm formation, quorum sensing pathway, and recent identified marine algae natural products as anti-biofilm agents will be discussed.